2020
DOI: 10.1186/s12889-020-09224-0
|View full text |Cite
|
Sign up to set email alerts
|

Housing as a social determinant of health and wellbeing: developing an empirically-informed realist theoretical framework

Abstract: Background: The role of housing as a social determinant of health is well-established, but the causal pathways are poorly understood beyond the direct effects of physical housing defects. For low-income, vulnerable households there are particular challenges in creating a sense of home in a new tenancy which may have substantial effects on health and wellbeing. This study examines the role of these less tangible aspects of the housing experience for tenants in the social and private rented sectors in west centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 44 publications
6
97
0
1
Order By: Relevance
“…Drawing upon previous literature [38][39][40], objective housing status included housing tenure, living space, housing conditions, and housing stability. Subjective housing status mainly included housing satisfaction.…”
Section: Independent Variables: Objective and Subjective Housing Statusmentioning
confidence: 99%
“…Drawing upon previous literature [38][39][40], objective housing status included housing tenure, living space, housing conditions, and housing stability. Subjective housing status mainly included housing satisfaction.…”
Section: Independent Variables: Objective and Subjective Housing Statusmentioning
confidence: 99%
“…Recent evidence has shown that adults who live alone are less likely to engage in healthy behaviors than their counterparts who live with others [31]. These findings highlight the importance of housing structure as a social determinant of health and its causal relationship to health outcomes [32]. To date, scant data is available regarding diabetes management adherence, a study from India showed that only 30 percent of patients taking oral anti-diabetic medication and insulin were checking their blood sugar levels regularly during the lockdown [33].…”
Section: Managing Diabetes During a Pandemicmentioning
confidence: 97%
“…Conditions of housing encompass issues such as overcrowding and sub-standard buildings, lack of access to safe drinking water and other utilities, ineffective waste disposal, poor quality sanitation infrastructure and inadequate provision of affordable and quality housing stock. The SDH literature has illustrated a clear relationship between housing and deleterious social health outcomes ( Krieger and Higgens 2002 ; Rolfe et al 2020 , Kang et al 2020 ). This is a global issue, but it is one that particularly impacts the estimated 1-1.6 billion people who live in slums and informal housing, a figure that represents around one-quarter of the world’s urban population ( Habitat for Humanity 2020 ).…”
Section: Social Determinantsmentioning
confidence: 99%
“…Our choice of SDs draws upon key factors that have been highlighted in the SDH literature ( Rolfe et al 2020 ; Braveman and Gottlieb 2014 ; Solar and Irwin 2010 ) but should be understood as merely illustrative of our broader argument. We recognise that a different range of SDs could be utilised, and also that social determinants of health are significantly co-constituted and mutually-reinforce one another (see the discussion of Solar and Irwin 2010 , pp.…”
Section: Introductionmentioning
confidence: 99%